2016
DOI: 10.1136/bmjopen-2015-010948
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education in the care of people diagnosed with dementia and their carers: a systematic review

Abstract: ObjectivesThis systematic review is linked to the multifaceted social, economic and personal challenges of dementia and the international recognition of the value of interprofessional education (IPE) and its influence on health and social care outcomes. This review therefore aimed to identify, describe and evaluate the impact of IPE interventions on health and social care practitioners (prequalification and postqualification) understanding of dementia, the quality of care for people with dementia and support f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
3
33
0
1
Order By: Relevance
“…Total payments in 2017 for all individuals with dementia were estimated to be $259 billion, approximately half of which is covered by Medicare and Medicaid. An additional $56 billion in out‐of‐pocket spending is borne by untrained caregivers, such as family and friends . With an average income of $45, 700, these caregivers report emotional and financial strain while providing assistance with daily activities, administering medical therapies, and providing direct care as well as navigating complex healthcare and social services systems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total payments in 2017 for all individuals with dementia were estimated to be $259 billion, approximately half of which is covered by Medicare and Medicaid. An additional $56 billion in out‐of‐pocket spending is borne by untrained caregivers, such as family and friends . With an average income of $45, 700, these caregivers report emotional and financial strain while providing assistance with daily activities, administering medical therapies, and providing direct care as well as navigating complex healthcare and social services systems .…”
Section: Introductionmentioning
confidence: 99%
“…The Workgroup made four recommendations to address areas of critical workforce gaps (Table 1), which were presented at the 2017 Summit. The areas of critical workforce gaps for which the recommendations proposed are: (1) recruitment and retention of a dementia-capable workforce, (2) financing and cost of workforce education and training, (3) interprofessional education and training for care coordination and management, and (4) translation and implementation of effective dementia care ( Figure 1). Table 2 includes recommended research focus areas to address these critical workforce gaps.…”
mentioning
confidence: 99%
“…It aimed to evaluate the impact of IPE education on health and social care practitioners and the care of service users and their carers. Jackson et al (2016) found no studies that assessed health outcomes. This supports the report by the Cochrane review (discussed above) there were a dearth of studies which were relevant (only 6) of which the evidence was weak due to sampling methods (convenience samples) and sample sizes combined with poor research design and therefore led to inconclusive results.…”
Section: Outcomes For Service Usersmentioning
confidence: 99%
“…Thistlethwaite notes evaluations of IPE focus on students learning and what they learn, but notably not health outcomes. Jackson et al (2016) completed a systematic review of IPE in the care of people with dementia. It aimed to evaluate the impact of IPE education on health and social care practitioners and the care of service users and their carers.…”
Section: Outcomes For Service Usersmentioning
confidence: 99%
“…A systematic review investigating the state of IPE in nursing concluded it was not possible to identify the best methodology for implementing it, particularly in relation to simulation and teaching methodologies 8. Another systematic review to evaluate whether IPE interventions increased practitioners' understanding of dementia concluded there was poor quality evidence to make any such associations 9. In addition, there is an absence of research on economic benefit as well as the effect on service users.…”
mentioning
confidence: 99%